Heteromeric Channels Formed From Alternating Kv7.4 and Kv7.5 α-Subunits Display Biophysical, Regulatory, and Pharmacological Characteristics of Smooth Muscle M-Currents - Brueggemann, Lyubov I.; Cribbs, Leanne L.; Byron, Kenneth L. (Frontiers in Physiology, 2020)
Smooth muscle cells of the vasculature, viscera, and lungs generally express multiple α-subunits of the Kv7 voltage-gated potassium channel family, with increasing evidence that both Kv7.4 and Kv7.5 can conduct “M-currents” that are functionally important for the regulation of smooth muscle contractility. Although expression systems demonstrate that functional channels can form as homomeric tetramers of either Kv7.4 or Kv7.5 α-subunits, there is evidence that heteromeric channel complexes, containing some combination of Kv7.4 and Kv7.5 α-subunits, may represent the predominant configuration natively expressed in some arterial myocytes, such as rat mesenteric artery smooth muscle cells (MASMCs). Our previous work has suggested that Kv7.4/Kv7.5 heteromers can be distinguished from Kv7.4 or Kv7.5 homomers based on their biophysical, regulatory, and pharmacological characteristics, but it remains to be determined how Kv7.4 and Kv7.5 α-subunits combine to produce these distinct characteristics. In the present study, we constructed concatenated dimers or tetramers of Kv7.4 and Kv7.5 α-subunits and expressed them in a smooth muscle cell line to determine what α-subunit configuration most closely matches the features previously reported for natively expressed Kv7 currents in MASMCs. Several unique characteristics of native smooth muscle M-currents were reproduced under conditions that constrain channel formation to a Kv7.4: Kv7.5 stoichiometry of 2:2, with alternating Kv7.4 and Kv7.5 α-subunits within a tetrameric structure. These findings provide new insights into the oligomerization of α-subunits and the ways in which Kv7.4/Kv7.5 subunit assembly can affect smooth muscle signal transduction and pharmacological responses to Kv7 channel modulating drugs.